2021
DOI: 10.3390/v13050819
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Postnatal Nutrition on Human T Cell Leukemia Virus Type 1 Mother-to-Child Transmission: A Systematic Review and Meta-Analysis

Abstract: The main route of mother-to-child transmission (MTCT) of human T cell leukemia virus type 1 is vertical transmission via breastfeeding. Although the most reliable method for preventing MCTC is exclusive formula feeding (ExFF), short-term breastfeeding (STBF) or frozen–thawed breast milk feeding (FTBMF) has been offered as an alternative method if breastfeeding is strongly desired. The aim of this review was to clarify the pooled risk ratio of MCTC of STBF and FTBMF compared with ExFF. This study was registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…2-4) [113]. The results suggest that STBF ≤ 3 months does not increase the risk of MTCT compared to ExFF, but the risk of MTCT may increase by approximately threefold if the duration of STBF is up to 6 months.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 77%
See 2 more Smart Citations
“…2-4) [113]. The results suggest that STBF ≤ 3 months does not increase the risk of MTCT compared to ExFF, but the risk of MTCT may increase by approximately threefold if the duration of STBF is up to 6 months.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 77%
“…Finally, 11 articles (i.e., 10 previous studies and our prospective cohort study [94]) were included in the meta-analysis. Six articles on the effect of STBF ≤ 3 months [94,[103][104][105][106][107], five articles on STBF ≤ 6 months [104,106,[108][109][110], and three articles on FTBMF [94,111,112] were included for the systematic review and meta-analysis [113]. The pooled relative risks of STBF ≤ 3 months, STBF ≤ 6 months, and FTBMF compared with ExFF were 0.72 (95% CI: 0.30-1.77; p = 0.48), 2.91 (95% CI: 1.69-5.03; p = 0.0001), and 1.14 (95% CI: 0.20-6.50; p = 0.88), respectively (Figures 2-4) [113].…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…co-infection; and access to safe, affordable formula feeding. A recent meta-analysis showed that short-term breastfeeding was not associated with a significant increase in the transmission of HTLV-1 [ 20 ]. However, the data were mainly restricted to Japan and may not be representative in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Itabashi et al conducted a prospective multicenter cohort study involving HTLV-1 carrier pregnant women and their infants as part of the Health, Labor, and Welfare Science Research Program in Japan to determine the rate of MTCT by ExFF, STBF, and FTBMF [ 56 ]. Miyazawa et al reported findings through a systematic review that integrated the results of the cohort study and previous studies [ 103 ].…”
Section: Strategies To Prevent Htlv-1 Mtctmentioning
confidence: 99%